"On the Way to Truth and Peace" (ep. 33, 6): Augustine's Anti-Donatist Readings of John 14, 27a - Grabau, Joseph (Editorial Uniagustiniana, 2019)
This chapter traces the development of Augustine's discourse on peace in light of anti-Donatist polemics found in both his earlier letters and formal treatises. First, it presents evidence of Augustine's effort to secure peace in North Africa from his letters; and second, the author focuses on Augustine's appeal to the Latin text of John 14:27a in light of contemporary social and ecclesial unrest. Whereas the first point of departure asks how Augustine's thoughts on upholding the public order appear at the level of social and political reflection, the second dimension turns to examine the concurrent role of biblical interpretation to a similar, yet distinct end. Both were essential forms of expressing his disagreements with Donatist views. In this way, the chapter demonstrates how the anti-Donatist message of peace was delivered along at least two supporting avenues: 1. Of promoting social stability through networking and letter exchange; and 2. Of promoting ecclesial unity and fidelity to Christ via biblical support. For Augustine, the pax Christi as described in this verse of the Gospel of John-unlike the pax Donati-provided for an authentic common good within time and history, as well as in the light of eternity. A Donatist notion of peace would appear to rest upon undervaluing the secular order and limited interpretation of John 14: 27a. In describing the Johannine gift of Christ as pax temporalis, however, Augustine remained aware that any form of peace achieved in the present was to be regarded as a passing and imperfect anticipation.